Character Association and Path Analysis for Growth, Physiological and Biochemical Traits of Casuarina Clones Under Salinity Stress - Garg, Rakesh Kumar; Bassi, Palwinder; Nicodemus, A.; Choudhary, O. P. Prakash; Kaur, Nirmaljit (Indian Forester, 2021)
Eight clones of Casuarina (four of Casuarina junghuhniana and four of interspecific hybrids of Casuarina equisetifolia Ã— C. junghuhniana) were subjected to saline water irrigation with different concentrations of NaCl viz., 0, 40, 80 and ;120 mM. After twelve months of study period, plant height, collar diameter, plant fresh weight, root length, proline, total soluble sugars reducing sugars, relative leaf water content, and Na+/K+ ratio showed high and positive correlation with plant dry weight. Path analysis revealed that collar diameter, root length, reducing sugars and relative leaf water content had the highest direct effect on plant dry weight and can be collectively used as selection criteria for improvement of Casuarina for increasing biomass.